Mining of Cryptocurrencies: Analysis of Law Enforcement Practice and Problem Solving in Legal Regulation - Svetlana Muradyan; Natalia Mikhaylenko; Anna Skachko; Yulia Ivanova; Elisei Rogachev; Elmir Alimamedov (Jurnal Cita Hukum, 2023)
Despite the enormous popularity of mining worldwide, which entirely objective reasons have caused, there remains a dissonance in States' approaches to its legal regulation. One of the reasons is that the legal regulation of blockchain technologies in different countries goes completely different ways. In fact, mining is a process of generating cryptocurrencies, as a result of which a new suitable block of transactions is added to the blockchain, and coins are issued. Therefore, to regulate such a process as mining, the legislator needs to create a holistic legal framework regulating the turnover of digital assets in the state.